The effect of lumbar-pelvic alignment and abdominal muscle thickness on primary dysmenorrhea - Baek, Il-hun; Goo, Bong-oh; Kim, Moon-jeong (Journal of Physical Therapy Science, 2016)
[Purpose] The purpose of this study was to identify effects of malalignment of the lumbar pelvis, as a passive element, and the thicknesses of abdominal muscles, as active elements, on primary dysmenorrhea. [Subjects and Methods] The subjects were divided into a primary dysmenorrhea group and normal group according to Visual Analogue Scale, and ultimately there were 28 subjects in the dysmenorrhea group and 22 subjects in the normal group. Alignment of the lumbar pelvis was measured by using a Formetric 4D analysis system, and the thicknesses of abdominal muscles were measured by using ultrasound imaging. [Result] Scoliosis was 6.7 ± 4.3° in the primary dysmenorrhea group and 3.8 ± 2.0° in the normal group, and the lordotic angles of the two groups were 0.6 ± 0.5° and 0.1 ± 0.3°, respectively. The thickness of the internal oblique was 3.8 ± 1.3 mm in the primary dysmenorrhea group and 6.0 ± 1.9 mm in the thicknesses of the transverse abdominis in the two groups were 2.6 ± 6.8 mm and 3.5 ± 6.1 mm, respectively. Furthermore, the thickness of the normal group, and the external oblique was 4.0 ± 0.8 mm in the primary dysmenorrhea group and 5.4 ± 1.4 mm in the normal group. [Conclusion] This study showed significant differences between the primary dysmenorrhea group and the normal group in lumbar-pelvic alignment and thicknesses of abdominal muscles.